GoMap: combining step counting technique with augmented reality for a mobile-based indoor map locator - Sharin, Nursyahirah Atikah; Mohd Norowi, Noris; Abdullah, Lili Nurliyana; Ng, Seng Beng (Institute of Advanced Engineering and Science, 2022)
In recent years, indoor navigation and localization has become a popular alternative to paper-based maps. However, the most popular navigation approach of using the global positioning satellite (GPS) does not work well indoors and the majority of current approaches designed for indoor navigation does not provide realistic solutions to key challenges, including implementation cost, accuracy, longer computation processes, and practicality. The step count method was proposed to solve these issues. This paper introduces GoMap - a mobile-based indoor locator map application, which combines the step counting technique and augmented reality (AR). The design and architecture of GoMap is described in this paper. Two small-scale studies were conducted to demonstrate the performance of GoMap. The first study found that GoMap’s performance and accuracy was comparable to other step counting app such as “Google Fit”. The second part of the study demonstrated the feasibility of the application when used in a real-world setting. The findings from the studies show that GoMap is a promising application that can help the indoor navigation process.